Adapting Practices from Qualitative Research to Tell a Compelling Story: A Practical Framework for Conducting a Literature Review - Kalpokas Matulaityte, Neringa; Radivojevic, Ivana (The Qualitative Report, 2021)
Despite the literature review being a common task for researchers, the actual process of conducting a quality literature review can easily be taken for granted. In effort to help qualitative researchers, this paper presents a practical framework for conducting a literature review that stems from qualitative research practices. As a literature review is essentially an analysis of rich textual information, qualitative research concepts, and skills can be creatively applied to the process of conducting a literature review. The present paper aims to share the fruits of qualitative analysis with researchers from all disciplines so that they may make sense of this rich information and tell a coherent and compelling story regarding their own analysis. In particular, this paper outlines foundational similarities between qualitative research and literature reviews and then proceeds to provide adaptable guidelines for connecting qualitative research skills to carrying out a rigorous literature review. We hope to incite curiosity and reflection on how qualitative research skills can be valuable beyond just analyzing qualitative data.
Keywords: Literature review; Best practices; Methodology; Qualitative research; 32 Ciencias Médicas; ODS 3 - Salud y bienestar; ODS 4 - Educación de calidad